Spill från rundbalspress med och utan knivar - Alfredsson, Håkan (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
When harvesteing ley there is always mechanical losses from the harvest machines. During the last years the roundbalers with knives,cutting the material-are more common, This use increase the mechanical losses of material. MATERIALS AND METHODS The roundbaler which used in this test was a Krone Vario Pack 1500 Multi Cut. This roundbaler has 17 knives. The theoretical length of cut was 64 mm. During the test we stretched a rubber tarp under the balechamber and collected the materials which fell down from the balechamber. We collected all of the material from the tarp after every bale and weighed the loss. The DM was tested in both the bale and the mechanical losses. RESULTS AND DISCUSSION The loss of material increased when we used 17 knives. The weight of the loss was 7,3 kg DM for a one round bale. When we didn´t use the knives the losses decreased to 1,3 kg DM. If you transform this sum to kg7ha by it was 80,6 kg/ha with the use of knives and 14,6 kg/ha without, which will be 2,1% and 0,3% of the crop harvested.